A Conceptual Framework for Research on Cognitive Impairment with no Dementia in Memory Clinic - Huang, Lin; Chen, Keliang; Liu, Zhao; Guo, Qihao (Current Alzheimer Research, 2020)
Background: Identifying and classifying individuals with Cognitive Impairment-No Dementia (CIND) has further challenged diagnostic methods, since varying the cutoffs for objective impairment as well as the neuropsychological tests considered can significantly affect diagnosis. Therefore, we investigated the applicability of an actuarial neuropsychological approach for clinical subdivision of CIND and quantified the variability in diagnostic outcomes that results from diverse neuropsychologically derived definition of objective cognitive impairment. Methods: 1459 non-demented, clinic-based individuals were recruited from a monocentric memory clinic from 1/1/2016/ to 1/1/2018 and classified as Cognitively Normal (NC), Slight Cognitive Symptom (SCS), SSubtle Cognitive Decline (SCD) or Mild Cognitive Impairment (MCI) via different diagnostic strategies, which varied the composition of objective cognitive assessments involved in the diagnostic process. Results: We compared two methods of criteria proposed by Jak/Bondi and Petersen/Winblad to classify individuals with CIND. A substantial range of differences in the percentages recognized as NC, SCS, SCD, and MCI was presented, depending on the classification criteria adopted. Our data revealed that the application of a set of six neuropsychological scores dividing CIND into 4 subgroups (NC, SCS, SCD, and MCI) was able to classify all non-demented individuals without overlap or omission. Conclusion: Our study provided clinical support for an operational framework of the CIND classification system and underlined the value of applying comprehensive neuropsychological assessments for definition. The concept of SCS, considered appropriate for a preclinical stage, was proposed as the symptomatic definition for early intervention.
Keywords: cognitive impairment with no dementia (CIND)